Controllable synthesis of SnO2 photocatalyst with superior photocatalytic activity for the degradation of methylene blue dye solution - Prakash, K.; Kumar, P. Senthil; Pandiaraj, S.; Saravanakumar, K.; Karuthapandian, S. (Journal of Experimental Nanoscience, 2016)
SnO2 photocatalyst was successfully synthesised by novel chemical route in hydrothermal environment and annealed at two different temperatures viz 550 and 600 degrees C, respectively. The crystal structure, optical properties, surface and bulk morphology have been characterised using various tools like X-ray diffraction (XRD), UV visible spectroscopy, Fourier transform infrared spectroscopy, transmission electron microscope (TEM) and scanning electron microscope (SEM). Cubic, spheres and porous like morphology of SnO2 photocatalyst was successfully confirmed using SEM micrographs and TEM. In addition to this the photocatalytic activity was evaluated towards the degradation of methylene blue dye solution. SnO2 photocatalyst annealed at 600 degrees C exhibits excellent photocatalytic efficiency which may be attributed to the unique morphology, high crystalline nature and charge separation. The photocatalyst efficiency was further tested towards the concentration of dye, catalyst dosage and pH of the dye. The involvement of center dot OH in the photocatalytic reaction was evidenced using trapping experiment by employing different scavengers. The photocatalyst was moderately active, stable upto its fifth usage and stability of the photocatalyst before and after the photocatalytic reaction was also been studied using XRD and SEM.